Pembelajaran Mahārat al-Kalām pada Program Kursus Bahasa Arab Spesial Ramadan di Pesantren Darul Lughah Waddirasatil Islamiyah, Pamekasan, Madura - Mahbub Humaidi Aziz; M. Syathibi Nawawi; Muhammad Alfan (Universitas Negeri Jakarta, 2020)
The purpose of this study was to determine the learning process (material, methods, media, and evaluation), effectiveness, and efficiency of learning mahārat al-kalām on the Ramadan Special Arabic course program at Pondok Pesantren Darul Lughah Waddirasatil Islamiyah (PP DLWI), Pamekasan, Madura. Data collection techniques used were observation, interviews, questionnaires, and documentation. Qualitative data were analyzed using descriptive methods, while quantitative data used simple statistics consisting of the stages of preparation, tabulation, and data processing. The results of this study prove that (1) the learning process of mahārat al-kalām consists of materials, methods, media, and evaluations that are tailored to each level; mubtadi’, mutawassiṭ, and mutaqaddim; (2) the effectiveness of mahārat al-kalām learning in this program is, the mubtadi’ level of 87.33% (very effective), the mutawassiṭ rate of 95.6% (very effective), and the mutaqaddim rate of 98% (very effective); (3) The efficiency of mahārat al-kalām learning in this program is, the mubtadi’ level of 88.25% (very efficient), the mutawassiṭ rate of 90.88% (very efficient), and the mutaqaddim rate of 94.05% (very efficient).